Understanding the perception of parents and professionals about Play-based early intervention for children with autism age 3-5 in Dhaka, Bangladesh." - Afreen, Masuma (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Education degree in Educational Leadership and School Improvement, 2024.